Survey of IP geolocation: theory, methods, and innovative applications - LIU Xueting; TAI Wenxin; ZHOU Fan; WANG Yong; CHEN Kai (Tongxin xuebao)
IP geolocation plays a critical role in determining the locations of cyberspace entities and is widely applied in important fields such as communication system optimization, financial risk prevention, and network topology mapping. The research papers in the field of IP geolocation over the past 20 years were reviewed systematically, the characteristics, advantages, and limitations of various approaches were analyzed, while exploring practical application scenarios and potential future development directions. The first comprehensive framework for IP geolocation technologies was also established in this review, different methods and paradigms were taxonomized, while the current challenges in accurate, trustworthy, and robust IP geolocations were analyzed. The goal is to provide theoretical and methodological support for future research, thereby promoting the further development and innovative applications of IP geolocation technologies.